Successful ICSI depends on DNA stability and disulfide status of sperm nuclei - Syahruddin Said; Koji Niwa (Indonesian Center for Animal Research and Development (ICARD), 2004)
Relation of successful ICSI (intracytoplasmic sperm injection) with DNA stability and thiol-disulfide status of rat spermatozoa nuclei was investigated. Testicular, caput and cauda epididymal spermatozoa have been used for this research. The nuclei of these spermatozoa were stained with aeridine orange for DNA stability test and labeled with mBBr for thiol-disulfide status before injesting into oocytes. Cauda epididymal spermatozoa were very stable and contained high disulfide than caput epididymal and testicular spermatozoa. Results from spermatozoa injection into oocytes show that they were capable to fertilize oocytes. However, testicular spermatozoa can not develop up to blastocyst stage. These results indicated that successful ICSI at least in the rat depends on DNA stability and disulfide status of sperm nuclei. Key words: ICSI, DNA stability, disulfide status, acridine orange, mBBr